2010
DOI: 10.1017/s0033822200045288
|View full text |Cite
|
Sign up to set email alerts
|

MICADAS: Routine and High-Precision Radiocarbon Dating

Abstract: ABSTRACT. The prototype mini carbon dating system (MICADAS) at ETH Zurich has been in routine operation for almost 2 yr. Because of its simple and compact layout, setting up a radiocarbon measurement is fast and the system runs very reliably over days or even weeks without retuning. The stability of the instrument is responsible for the good performance in highestprecision measurements where results of single samples can be reproduced within less than 2‰. The measurements are described and the performance of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
218
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(231 citation statements)
references
References 22 publications
2
218
1
Order By: Relevance
“…The samples were subsequently neutralized and dried over NaOH pellets to remove residual acid. The sample was then wrapped in tinfoil boats (Elementar), pressed, and 335 analysed using a coupled elemental analyser-isotope ratio mass spectrometer-accelerator mass spectrometer (EA-IRMS-AMS) system at ETH Zurich Wacker et al, 2010). The instrumental set-up, blank assessment, accuracy, and reproducibility for the data presented here have been previously reported in McIntyre et al (2016).…”
Section: Bulk Elemental and Isotopic Analysismentioning
confidence: 99%
“…The samples were subsequently neutralized and dried over NaOH pellets to remove residual acid. The sample was then wrapped in tinfoil boats (Elementar), pressed, and 335 analysed using a coupled elemental analyser-isotope ratio mass spectrometer-accelerator mass spectrometer (EA-IRMS-AMS) system at ETH Zurich Wacker et al, 2010). The instrumental set-up, blank assessment, accuracy, and reproducibility for the data presented here have been previously reported in McIntyre et al (2016).…”
Section: Bulk Elemental and Isotopic Analysismentioning
confidence: 99%
“…Based on these experiments, a mean analytical procedure blank correction factor and SD of 1.0 ± 0.1 µg modern C (see below) per sample was obtained, and it was adopted for all aerosol filters. The 14 C / 12 C ratios were also corrected for isotopic fractionation by using the 13 C / 12 C ratios (Wacker et al, 2010) that were obtained simultaneously in the actual AMS measurements. The 14 C / 12 C isotopic ratios derived were also normalized to that of the oxalic acid II standard reference material (NIST 4990C, USA), and the measurement results were expressed as fraction of modern carbon (f M ), which denotes the 14 C / 12 C ratio of the samples relative to that of the unperturbed atmosphere in the reference year of 1950 (Burr and Jull, 2009).…”
Section: Analyses Of Aerosol Samples and Data Treatmentmentioning
confidence: 99%
“…It has been demonstrated that 14 C can be measured with precision in the per mil range (Goslar et al 2004;Synal and Wacker 2010;Wacker et al 2010). This aspect has been a topic in many other papers and is therefore not discussed here.…”
Section: Resultsmentioning
confidence: 99%